Drilling and installation of boreholes for permafrost thermal monitoring on Livingston Island in the maritime Antarctic - Ramos, Miguel (2009)
Three new boreholes up to 25 m deep were drilled on Mount Reina Sofı ́a (275 m a.s.l.), LivingstonIsland, where previous near-surface temperature measurements (mean annual ground temperatures of 2.1 to 2.68C) have indicated the presence of permafrost. A thermistor chain and logging systemwere installed in the deepest borehole, while the others were equipped with individual miniaturetemperature loggers (iButtons). Initial data from the 25 m borehole indicates a permafrost body severaldecametres thick. Future data from these boreholes are expected to provide insight into groundtemperature evolution in maritime Antarctica.